Software project management - Zakaria, Mohd. Hafiz; Mohd. Sanusi, Nurazlina; Yusof, Robiah; Ahmad, Sabrina (Penerbit UTeM Press, 2007)
This module aims to equip students with software for project management using Microsoft Project. Students will learn how to use the top project management software tool in the industry. The module will teach students how to manage IT project management in general and interactive media project management.